Prevalence and characteristics of psychiatric morbidity treated in specialized health care in a nationwide cohort of people with newly diagnosed Alzheimer's disease - Alastalo Aleksi; Tolppanen Anna-Maija; Nietola Mika; Haapea Marianne; Miettunen Jouko; Hartikainen Sirpa; Jääskelainen Erika (WILEY, 2022)
Objective: Psychiatric disorders have been implied as both risk factors and prodromal symptoms of Alzheimer's disease (AD). A better understanding of the history of psychiatric morbidity in people with AD may aid with understanding this relationship and highlight challenges in diagnosing AD in people with concomitant psychiatric disorders.
Methods: Medication use and Alzheimer's disease (MEDALZ) study is a nationwide register-based cohort of people (n = 70,718) who received a clinically verified AD diagnosis in Finland in 2005-2011 and were community-dwelling at the time of diagnosis. The study population was divided into four groups based on psychiatric morbidity treated in specialized health care. We characterized the groups using data of psychiatric and somatic illnesses, psychotropic drug use, and socioeconomic factors and investigated factors associated with prodromal AD.
Results: Altogether, 4.3% of cohort members had a psychiatric diagnosis at least five years before AD diagnosis, 3.1% had a psychiatric diagnosis only up to five years before AD diagnosis, and 1.1% had a psychiatric diagnosis both less and more than 5 years before AD. Belonging to the Prodromal group (psychiatric diagnosis within 5 years before AD diagnosis) was most strongly associated with substance abuse (RR 65.06, 95%CI 55.54-76.22). Other associated factors with the Prodromal group were female gender, use of psychotropics, stroke, and asthma/COPD.
Conclusion: Substance abuse and psychotropic drug use are common five years before AD diagnosis. These can be potential markers of possible prodromal symptoms of AD and should be acknowledged in clinical work.